2016
DOI: 10.1007/s00122-015-2647-1
|View full text |Cite
|
Sign up to set email alerts
|

The triploid East African Highland Banana (EAHB) genepool is genetically uniform arising from a single ancestral clone that underwent population expansion by vegetative propagation

Abstract: All East African Highland Banana varieties are genetically uniform having arisen from a single clone introduced to Africa. East African Highland bananas (EAHBs) are a subgroup of triploid (AAA genome) bananas of importance to food security in the Great Lakes region of Africa. Little is known about their genetic variation, population structure and evolutionary history. Ninety phenotypically diverse EAHB cultivars were genotyped at 100 SSR microsatellite markers to investigate population genetic diversity, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 63 publications
6
61
0
Order By: Relevance
“…However, Creste et al (2003), using SSR to analyze 35 polyploid banana cultivars (3x AAA, AAB; 4x AAAA, AAAB) grown in Brazil, concluded that their phenetic analysis based on the Jaccard similarity index highly agreed with the morphological classification. Kitavi et al (2016) used 100 SSR markers to investigate the genetic diversity of 90 phenotypically diverse EAHB cultivars collected from Kenya and Uganda and compared them with plantain (AAB) and dessert (AAA) cultivars. They found out that EAHB cultivars had minimal genetic variation and were largely genetically uniform, irrespective of source of collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, Creste et al (2003), using SSR to analyze 35 polyploid banana cultivars (3x AAA, AAB; 4x AAAA, AAAB) grown in Brazil, concluded that their phenetic analysis based on the Jaccard similarity index highly agreed with the morphological classification. Kitavi et al (2016) used 100 SSR markers to investigate the genetic diversity of 90 phenotypically diverse EAHB cultivars collected from Kenya and Uganda and compared them with plantain (AAB) and dessert (AAA) cultivars. They found out that EAHB cultivars had minimal genetic variation and were largely genetically uniform, irrespective of source of collection.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a previously assumed fifth clone set (Mbidde), containing only bananas for beer making, has recently been abandoned (Kitavi et al 2016), its cultivars being morphologically and genetically indistinguishable from one or other of the aforementioned clone sets. Our results are in line with Kitavi et al (2016) findings that the four clone sets are part of a single subgroup stemming from a single original AAA hybrid that has probably been formed in eastern Indonesia (Perrier et al 2011) and diversified subsequently by multiple somatic mutations. A similar conclusion can be made for the subgroup of AAB 'African Plantains' that is subdivided into three clone types: Horn, False Horn and French, based on inflorescence morphology .…”
Section: Triploid Cultivarsmentioning
confidence: 99%
“…Risterucci et al 2009). Yet SSR markers are still used as an effective tool in elucidating the genetic diversity in many plant species, including bananas (Nicolai et al 2013;Mbanjo et al 2012;Gross-German and Viruel 2013;Liu et al 2015;Kitavi et al 2016). The main advantage of the SSR genotyping approach resides in its capability of systematically adding new information to existing data sets.…”
mentioning
confidence: 99%
“…Variation in rainfall patterns impacts banana production by causing drought stress because most farmers in the region rely on rain for agricultural production. Although phenotypic variation is observed in EAHB, their genetic variation is low [9, 10] making them all susceptible to biotic and abiotic stress. Adaptation of cultivated banana varieties to changing environment is limited because while some are capable of sexual reproduction, they are all propagated clonally.…”
Section: Introductionmentioning
confidence: 99%